Pricing of gas swing options using Monte Carlo methods - Andrea Klimešová; Tomáš Václavík (Charles University in Prague, Institute of Economic Studies (IES), 2011)
Motivated by the changing nature of the natural gas industry in the European Union driven by the liberalization process, we focus on pricing of gas swing options. These options are embedded in typical gas sales agreements in the form of offtake flexibility concerning volume and time. The gas swing option is actually a set of several American puts on a spread between prices of two or more energy commodities. This fact together with the fact that the energy markets are fundamentally different from traditional financial security markets is important for our choice of valuation technique. Due to the specific features of the energy markets, the existing analytic approximations for spread option pricing are hardly applicable to our framework. That is why we employ Monte Carlo methods to model the spot price dynamics of the underlying commodities. The price of an arbitrarily chosen gas swing option is then computed in accordance with the concept of risk-neutral expectations. Finally, our result is compared with the real payoff from the option realized at time of the option execution and the maximum ex-post payoff the buyer could generate in case he knew the future, discounting to the original time of the option pricing.
Keywords: C63; G12; G13; 330; energy markets; gas sales agreement; gas swing option; Monte Carlo simulations; spread option pricing